Discrepancy between frequency domain optical coherence tomography and intravascular ultrasound in human coronary arteries and in a phantom in vitro coronary model. (15th October 2016) - Kim, In-Cheol; Nam, Chang-Wook; Cho, Yun-Kyeong; Park, Hyoung-Seob; Yoon, Hyuck-Jun; Kim, Hyungseop; Chung, In-Sung; Han, Seongwook; Hur, Seung-Ho; Kim, Yoon-Nyun; Kim, Kwon-Bae
Abstract: Background: This purpose of this study is to evaluate, concomitantly with quantitative coronary angiography (QCA), the potential discrepancy between frequency domain optical coherence tomography (FD-OCT) and intravascular ultrasound (IVUS) measurements in a phantom coronary model and in human coronary arteries within and outside stented segments. Methods: FD-OCT and IVUS images sequentially obtained from a phantom coronary model and 57 stented human coronary arteries were compared between each other and with QCA. Results: Lumen area (LA) by IVUS was 10.1% larger (6.43 ± 0.09 mm 2 ) while by FD-OCT was similar (5.78 ± 0.09 mm 2 ) to actual phantom LA (5.72 mm 2 ); IVUS vs. FD-OCT stent area (SA) was 4.2% larger. In human coronary artery, diameter by QCA was smaller than by IVUS and OCT in reference (by 10.5% and 3.5%, both p < 0.001) and stented (3.6%, p < 0.001; and 1.7%, p = 0.012) segments. IVUS vs. FD-OCT distal reference LA was significantly larger (6.19 ± 2.18 mm 2 vs. 5.49 ± 2.49 mm 2, p < 0.001, respectively), and SA was numerically larger (7.42 ± 2.28 mm 2 vs. 7.22 ± 2.48 mm 2, p = 0.059) with larger discrepancy in reference (11.3%) than stented (2.7%) segments. IVUS vs. FD-OCT correlation for diameter was significantly higher for stented than reference segments (R 2 = 0.8670 vs. 0.7351, p = 0.047), while numerically higher for area (R 2 = 0.8663 vs. 0.7806, p = 0.157). Conclusions: In phantom model and human coronary arteries, IVUS vs. FD-OCT measurements were larger, particularly in non-stented than stented segments, and diameter was smaller by QCA vs. IVUS or FD-OCT. Despite undefined clinical significance, said discrepancy warrants consideration.